Successful implementation of an appendectomy process improvement protocol. Issue 1 (17th June 2019) - Bradley, Matthew; Kindvall, Angela; Logan, Judy; Bailey, Jeffrey; Elster, Eric; Rodriguez, Carlos
Abstract : Background: A key component of a process improvement program is the institution of hospital-specific protocols to address certain disparities and streamline patient care. In that regard, we evaluated the implementation of an outpatient laparoscopic appendectomy (OLA) protocol at a tertiary military hospital. We hypothesized that OLA would reduce length of stay (LOS) without increasing complications. Methods: In August 2016, our institution implemented an OLA protocol—defined as discharge within 24 hours of surgery. Exclusion criteria included age <18 years old, grade 4 or 5 appendicitis, immunosuppression, current pregnancy, and no supervision during the first 24 hours postdischarge. To determine OLA's effect on LOS, analysis of variance was used to perform a comparison between the years 2014 and 2017. Successful outpatient appendectomies were recorded preprotocol and postprotocol, as well as readmission complications. Results: In 2017, the first full year of protocol implementation, 44 of 59 (75%) patients met the inclusion criteria, and all but 2 (42 of 44, 95%) stayed for less than 24 hours. Of the two outliers, one developed acute on chronic kidney disease and one had a slow return of bowel function following grade 3 appendicitis. Complications were low across all years (one per year). In 2017, the readmission was for percutaneous drainage of an abscess. Overall, protocol implementation produced a significant decrease in LOS. Discussion: OLA protocol decreased LOS at a military hospital and should be expanded to other department of defense (DoD) facilities. Further research is needed to identify cost benefit to the military health system. Level of evidence: III.